Emotion regulation and psychopathology : a transdiagnostic approach to etiology and treatment - Kring, Ann M.; Sloan, Denise M. (Guilford Press, 2010)
Regardless of their specific diagnosis, many people seeking treatment for psychological problems have some form of difficulty in managing emotional experiences. This state-of-the-art volume explores how emotion regulation mechanisms are implicated in the etiology, development, and maintenance of psychopathology. Leading experts present current findings on emotion regulation difficulties that cut across diagnostic boundaries and present psychotherapeutic approaches in which emotion regulation is a primary target of treatment. Building crucial bridges between research and practice, chapters desc.